Position Error Analysis of the Vehicle-borne Radar Array Lifting Device - Kang Wei; Bao Hanwei; Jiang Xiaoshuai; Sun Qipeng; Li Gangyan (Jixie chuandong)
Taking the radar vehicle- borne array lifting device as the research object,combing with the engineering practice,adopting the combination of theoretical derivation and simulation research method,an analysis method for the position error of array lifting device is proposed,and the causes and influencing factors of the position error of array lifting device are analyzed. Finally,by using MATLAB software,the simulation calculation is carried out,the position errors of array lifting device are obtained,the influence of the main parameters on the position error is analyzed,and theoretical basis for the design and control of the position accuracy of the array lifting device is provided,and the research results have some engineering significance.